Multi-criteria site selection for offshore renewable energy platforms. (March 2016) - Cradden, L.; Kalogeri, C.; Barrios, I. Martinez; Galanis, G.; Ingram, D.; Kallos, G.
Abstract: Geographical Information Systems (GIS) are commonly used in renewable energy resource analysis to establish optimal locations for development. Previous work focuses either on a single technology with fixed site-selection criteria, or on small, localised areas. The potential for combining or co-locating different offshore energy technologies, particularly over a large region, has been explored previously but at a relatively low level of detail. Here, bespoke resource data from high resolution co-located, co-temporal wind and wave models are presented in a GIS with a range of additional environmental and physical parameters. Dedicated decision-support tools have been developed to facilitate flexible, multi-criteria site selections specifically for combined wind-wave energy platforms, focusing on the energy resources available. Time-series tools highlight some of the more detailed factors impacting on a site-selection decision. The results show that the main potential for combined technologies in Europe is focused to the north and west due to strong resources and acceptable depth conditions, but that there are still obstacles to be overcome in terms of constructability and accessibility. The most extreme conditions generally coincide with the maximum energy output, and access to these sites is more limited. Highlights: A bespoke European wind, wave and tidal energy resource dataset was built into a GIS. Unique flexible tools were created to identify sites for offshore energy platforms. Time series were used to examine detailed met-ocean factors including correlation. The north and west of Europe most suitable in terms of energy and depth requirements. Accessibility and logistics are likely to be problematic at promising sites.